At the Intersection of Corporate Social Irresponsibility, Gender, and Race: Millennial and Gen Z Consumer Loyalty - Turner, Frances; Marar Yacobian, Marianne; Zaima, Janis (Archives of Business Research, 2022)
Corporations are under increasing scrutiny by stakeholders regarding whether their activities do good or do bad. This study explores perceptions of corporate social irresponsibility (CSiR) at the intersection of race and gender among Millennial and Gen Z women and people of color (POC). It considers the effect these groups’ sentiments exert on consumer behavior and loyalty. Results suggest race is the predominant identity shaping repeated patronage of a company. Intra-racial similarities were more noteworthy than intra-gendered assessments. This research advances literature on CSiR, multiracial marketing, and Millennial and Gen Z consumers, offering guidance regarding firms’ socially responsible actions.